Impact of Graphene/Nanocellulose on Nanocomposite Membrane for Methylene Blue Dye Removal and Antifouling Performance - Md Rezaur, Rahman; Ain Zaienah, Sueraya; Khairul Anwar, Mohamad Said; Murtala, Namakka; Anthonette, James; Ismail Md. Mofizur, Rahman; Muneera S. M., Al-Saleem; Jehan Y., Al-Humaidi; Mohammed Muzibur, Rahman (Wiley Periodicals LLC, 2025)
The development of membrane technologies in improving water purification systems has been extensively studied by many researchers to ensure efficient production of clean water sources. However, fouling of PVDF membrane results in low permeation and dye removal efficiency, causing a major issue in membrane production. To mitigate this issue, graphene (GR) and nanocellulose (NC) were incorporated in PVDF membrane to improve the membrane performance, as both nanoparticles have unique hydrophilicity properties and high mechanical strength. The nanocomposite membranes were fabricated via phase inversion method with PVDF as the polymer and N-methyl-2-pyrrolidone (NMP) as the solvent. The nanocomposite membranes were characterized by using field emission scanning electron microscopy equipped with energy dispersive x-ray spectroscopy (FESEM-EDX), x-ray diffraction (XRD), transmission electron microscopy (TEM), and ultraviolet–visible spectroscopy (UV–Vis) analysis. The FESEM analysis showed that 20% GR and 30% GR nanocomposite membranes were highly porous with uniform dispersion without agglomeration, which results in enhanced membrane permeation and separation efficiency. The XRD analysis indicated that all the nanocomposite membrane ratios retained the crystalline structure of PVDF at 2θ values of 18.21°, 19.20°, and 26.6°, except for 20% GR and 30% GR. In addition, the membrane permeability was evaluated by conducting water flux and MB dye removal tests. The water flux test revealed that 20% GR has the best water flux of 435.15±1.73L/m2⋅h⋅bar, which is four times higher than the pristine membrane with 110.87±2.50L/m2⋅h⋅bar. Additionally, 20% GR also exhibited the highest dye removal efficiency amounting to 94.47% (±0.18). Moreover, 20% GR demonstrated superior antifouling properties, which also resulted in excellent reusability, highlighting its potential for enhanced water purification in dye removal.